Synthetic Biology and Metabolic Engineering Approaches and Its Impact on Non-Conventional Yeast and Biofuel Production - Madhavan, Aravind; Jose, Anju Alphonsa; Binod, Parameswaran; Sindhu, Raveendran; Sukumaran, Rajeev K.; Pandey, Ashok; Castro, Galliano Eulogio (Frontiers in Energy Research, 2017)
The increasing fossil fuel scarcity has led to an urgent need to develop alternative fuels. One of the most promising alternatives to petroleum for the production of fuels is microbial production. Yeasts are highly efficient producer of bioethanol with several superior traits over bacterial counterparts. Tools of synthetic biology has revolutionised the field of microbial cell factories especially in the case of ethanol and fatty acid production. Era of yeast synthetic biology began with the well-studied industrial work horse Saccharomyces cerevisiae. Despite many highly beneficial traits like ethanol tolerance, thermotolerance, inhibitor tolerance, genetic diversity, non-conventional yeast has for synthetic biology, it currently lags behind Sachharomyces cerevisiae in the number of synthetic networks that have been described. Currently synthetic biology is slowly widening to the non-conventional yeasts like Hansenula polymorpha, Kluyveromyces lactis, Pichia pastoris and Yarrowia lipolytica. Here we review basic synthetic biology tools that we can apply to non-conventional yeasts. Moreover we discuss how metabolic engineering and synthetic biology tools can be applied in nonconventional yeasts for improved biofuel production.